Ironclad Apps: End-to-End Security via Automated Full-System Verification - Hawblitzel, Chris; Howell, Jon; Lorch, Jay; Narayan, Arjun; Parno, Bryan; Zhang, Danfeng; Zill, Brian (USENIX Symposium on Operating Systems Design and Implementation (OSDI), 2014)
An Ironclad App lets a user securely transmit her data to a remote machine with the guarantee that every instruction executed on that machine adheres to a formal abstract specification of the app’s behavior. This does more than eliminate implementation vulnerabilities such as buffer overflows, parsing errors, or data leaks; it tells the user exactly how the app will behave at all times. We provide these guarantees via complete, low-level software verification. We then use cryptography and secure hardware to enable secure channels from the verified software to remote users. To achieve such complete verification, we developed a set of new and modified tools, a collection of techniques and engineering disciplines, and a methodology focused on rapid development of verified systems software. We describe our methodology, formal results, and lessons we learned from building a full stack of verified software. That software includes a verified kernel; verified drivers; verified system and crypto libraries including SHA, HMAC, and RSA; and four Ironclad Apps.